Relationship Between Work Family Conflict with Commitment Organization - Rozana, Anna; Dwarawati, Dinda; Utami, Ayu Tuty; Ramadhita, Della; Ranchman, Nindy Puspita; Nurizqi, Luthfiah; Aditya, Arya (KnE Social Sciences, 2023)
Female lecturers play dual roles as both mothers responsible for home activities and family management and as workers responsible for their job performance. Balancing these roles is crucial for optimal functioning. Organizational commitment is essential for lecturers to actively engage, maintain their involvement, and achieve organizational goals. However, this dual role also makes them susceptible to work-family conflicts when they struggle to strike a balance between their roles as mothers and workers. This study aims to examine the impact of work-family conflict on the organizational commitment of female lecturers in higher education. It is a non-experimental quantitative research, and the data will be analyzed using multiple linear regression. The work-family conflict scale by Carlosn & Kacmar, adapted by Kuntari, and the organizational commitment measurement tool developed by Ingarianti were used for data collection. The research output will be published in the Psikostudia psychology journal of Mulawarman University. Keywords: work family conflict, organizational commitment, female lecturer, universities